The state of circular economy implementation in the building and construction sector in Aotearoa New Zealand - Cossar LC; Hytten KF; Hannon J; de Miguel Mercader F (Elsevier, 2026)
The building and construction sector places immense pressure on the environment, contributing significantly to resource extraction, global greenhouse gas emissions, and the loss of ecosystems and biodiversity. In this context, the B&C sector can both contribute to, and benefit from, a global shift towards a circular economy (CE), moving away from unsustainable linear consumption patterns that degrade vital ecosystem services. However, little is known about the extent to which B&C businesses implement circular strategies in many countries. This study aimed to assess the current level of implementation of circular strategies among businesses within Aotearoa New Zealand's B&C sector. An exploratory sequential mixed-methods research design was utilised. Experts from seven business types (manufacturing, architecture and engineering, construction, design-build, fit-out, demolition, and waste management companies) were interviewed to explore the relevance and uptake of circular strategies from the literature. This informed a survey distributed to professionals across the seven business types. Most circular strategies were considered relevant by interviewees and were subsequently included in the survey. Interviewees suggested that CE implementation is currently insufficient, inconsistent, uncoordinated, and limited to a narrow focus on recycling. According to survey responses from 213 professionals, most businesses are at a ‘beginner’ stage of maturity regarding CE implementation, and most circular strategies receive minimal to moderate levels of implementation. In particular, service-based models, sharing platforms, material passports, remanufacturing, take-back schemes, organic recycling, and regenerating nature require greater attention. These findings suggest that CE implementation in Aotearoa New Zealand's B&C sector is still nascent, with significant potential to increase engagement in circular strategies. Findings also underscore the necessity for greater education, a stronger emphasis on the design phase, and a systemic, collaborative approach to accelerate the transition towards a CE.